2023
DOI: 10.31616/asj.2022.0162
|View full text |Cite
|
Sign up to set email alerts
|

Does Bracing Control the Progression of Adolescent Idiopathic Scoliosis in Curves Higher Than 40°? A Systematic Review and Meta-analysis

Abstract: Routinely, adolescent idiopathic scoliosis (AIS) curves that progress beyond 40° in skeletally immature adolescents require surgery. However, some adolescents with AIS and their parents utterly refuse surgery and insist on wearing a brace. Debate continues regarding the appropriateness of bracing for AIS curves exceeding 40° in patients who have rejected surgical intervention. This systematic review and meta-analysis was conducted to review the literature on the effectiveness of bracing and its predictive fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, some children with AIS and their parents refuse surgery altogether and insist on wearing a brace. Recently published meta-analyses have shown that bracing can also stop the natural history of scoliosis curves from 40° to 60° ( 6 ). In recent years, a growing number of high-quality randomized controlled trials have demonstrated the positive short-term effects of Physiotherapeutic Scoliosis-specific Exercises (PSSE) in the treatment of AIS ( 7 , 8 ), whereas the effectiveness of the long-term effects is unclear, and usually, PSSE is used as a support for the treatment of AIS.…”
Section: Introductionmentioning
confidence: 99%
“…However, some children with AIS and their parents refuse surgery altogether and insist on wearing a brace. Recently published meta-analyses have shown that bracing can also stop the natural history of scoliosis curves from 40° to 60° ( 6 ). In recent years, a growing number of high-quality randomized controlled trials have demonstrated the positive short-term effects of Physiotherapeutic Scoliosis-specific Exercises (PSSE) in the treatment of AIS ( 7 , 8 ), whereas the effectiveness of the long-term effects is unclear, and usually, PSSE is used as a support for the treatment of AIS.…”
Section: Introductionmentioning
confidence: 99%
“…The younger the age and the larger the curvature, the greater the risk of curvature progression. Observation and bracing are the most widely accepted nonoperative treatments for mild to moderate curves, whereas operative treatment is required for Cobb angles of 50 degrees or more [3,4]. Various surgical methods exist, but posterior spinal fusion surgery using pedicle screws is commonly and widely performed.…”
Section: Introductionmentioning
confidence: 99%
“…A moderate curve is between 25 degrees and 40 degrees. A severe curve is more than 40 degrees [15,16]. The instrumental diagnosis of AIS based on a frontal curve of the spine is greater than 10 • Cobb, as measured on a postero-anterior (P-A) spine radiograph (X-ray) [17].…”
Section: Introductionmentioning
confidence: 99%